A rare case of double ectopic thyroid without orthotopic thyroid gland. Issue 2 (March 2015) - Singh, Gautam Bir; Kumar, Deepak; Ranjan, Shruti; Tomer, Shaili
Abstract: We report an extremely rare case of concurrent lingual thyroid and thyroglossal duct thyroid without orthotopic thyroid gland in a paediatric patient with hypothyroidism. The clinical record highlights the importance of ultrasonography and thyroxine therapy in the management of this rare clinical entity.